Making a Neolithic Non-Megalithic Monument : a TRB Burial Ground at Dalfsen (the Netherlands), c. 3000-2750 cal. BC - Velde, H. M. van der; Bouma, N.; Raemaekers, D. C. M. (Sidestone Press, 2022)
In 2015 at Dalfsen (the Netherlands) archaeologists made an amazing discovery. They found a burial ground dating from the TRB-period (3000-2750 BC) comprising 141 burial pits. The TRB is dated in the last phase of the Middle Neolithic period and is well known for its megalithic monuments which are widespread through large parts of northern Europe. Until recently few non-megalithic burial grounds were known and the find of the Dalfsen burials created new opport.